Cosmographic analysis of a model of the pulsating universe with diverse types of matter - Altayeva, G.S.; Razina О.V.; Tsyba, P.Yu.; Altaibayeva, A.B. (Recent Contributions to Physics, 2023)
In this paper, a model of a pulsating universe is investigated with periodic function of the scale factor together with a homogeneous, isotropic and spatially flat Friedman-Robertson-Walker metric. The parameters of the pulsating universe model coincide with observation parameters of the modern universe, taking into account the different contributions of various types of matter to its evolution. In the resulting solution, during periods of accelerated expansion of the universe, the scalar field with negative pressure makes a greater contribution to the expansion growth. The fermionic field and the vector field, which have positive pressure values during this period, prevent the growth of this expansion. During periods of compression, the fermionic field and the vector field have a greater influence on the dynamics of the evolution of the universe. In the resulting periodic solution, the universe goes through endless cycles of expansion and contraction. The observed modern accelerated expansion of the universe corresponds to one of these cycles. Cosmographic parameters are calculated - parameters of deceleration q, jerk j and snap s and energy conditions for the model under research. These parameters make it possible to link model-independent results obtained from cosmography with theoretically sound assumptions of gravity.